The transmission of supply shocks in different inflation regimes - Arndt, Sarah; Enders, Zeno (CESifo working papers, 2023)
We show that the impact of supply and monetary policy shocks on consumer prices is state-dependent. First, we let the data determine two inflation regimes and find that they are characterized by high and low inflation volatility. We then identify upstream supply shocks using instrumental variables based on data outliers in the producer price series. Such shocks exhibit a more substantial and more persistent effect on downstream prices during periods of elevated inflation volatility (State 2) compared to phases of more stable consumer price growth (State 1). Similarly, monetary policy shocks are more effective in State 2. Exogenously differentiating regimes by the level of inflation or the shock size does not reveal state dependency. The evidence supports a model in which producers invest in price flexibility. This model predicts that stricter inflation targeting reduces price flexibility and, consequently, the pass-through of all shocks to inflation, beyond the standard channel that affects demand.